4 A life or 'good death' situation? A worldwide ecological study of the contexts of countries which have and have not implemented palliative care. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Clark, Joseph; Barnes, Amy; Campbell, Mike; Gardiner, Clare
Abstract : Background: Palliative Care (PC) advocates argue that service implementation is feasible in all settings. Yet, services have developed patchily in low and middle-income settings. Beyond Human Development Index indicators, little thought has been given to the broader development challenges facing nations tasked with implementing PC. Aim: To describe how indicators of national development relate to levels of PC services in nations around the world. Methods: An ecological study to identify relationships between potential predictor variables and countries' level of PC development. 28 predictor variables from 6 domains were selected using hypothesised relationships with levels of PC development: disease demographics, socioeconomics, health systems, politics, demographics and economics. The outcome variable was level of national PC development on a six-point scale. Spearman's correlation test was used, significance level <0.05. Results: 26/28 variables were significantly associated with levels of PC development in 207 countries. PC is more developed in countries with high: percentage of deaths from non-communicable disease, population proportion aged 65+, gross national income and tourism. Development is lower in countries with high levels of: political corruption, infant mortality, deaths by infectious disease and weak democracy. Prevalence of undernourishment and levels of private health expenditure were not associated with PC development. Discussion: PC development is highly consistent with broader national development indicators. Development is less in countries where acute deaths are more likely and any benefits from PC provision, short-term. In such countries, resources may be prioritised towards life prolonging therapies and key aspects of PC need only, prior to fully integrated palliative services. Calls for accelerated development of PC services must be informed by in-depth understanding of national development contexts, local needs and opportunity costs.